2018
DOI: 10.1111/syen.12284
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial phylogenomics, the origin of swallowtail butterflies, and the impact of the number of clocks in Bayesian molecular dating

Abstract: Swallowtail butterflies (Lepidoptera: Papilionidae) have been instrumental in understanding many foundational concepts in biology; despite this, a resolved and robust phylogeny of the group has been a major impediment to elucidating patterns and processes of their ecological and evolutionary history. This study presents a mitogenomic, time‐calibrated phylogeny for all swallowtail genera. A shotgun sequencing approach was performed to obtain 32 complete mitogenomes that were added to available butterfly mitogen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
44
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 40 publications
(49 citation statements)
references
References 118 publications
4
44
0
1
Order By: Relevance
“…Recently, Condamine et al . () noted “within Papilioninae, our results support earlier morphological results (Munroe & Ehrlich ; Munroe ) by recognizing four monophyletic and well‐supported tribes: Leptocircini, Teinopalpini, Papilionini and Troidini. We further found that Leptocircini is the sister clade to all other Papilioninae, and that Teinopalpini is sister to Papilionini plus Troidini.…”
Section: Introductionsupporting
confidence: 90%
See 4 more Smart Citations
“…Recently, Condamine et al . () noted “within Papilioninae, our results support earlier morphological results (Munroe & Ehrlich ; Munroe ) by recognizing four monophyletic and well‐supported tribes: Leptocircini, Teinopalpini, Papilionini and Troidini. We further found that Leptocircini is the sister clade to all other Papilioninae, and that Teinopalpini is sister to Papilionini plus Troidini.…”
Section: Introductionsupporting
confidence: 90%
“…; Condamine et al . ). Speculation that Aristolochiaceae‐feeding represents the ancestral condition within Parnassiinae + Papilioninae was rejected by Miller () and Weintraub () based on cladistic analyses.…”
Section: Introductionmentioning
confidence: 97%
See 3 more Smart Citations